2015
DOI: 10.1111/jphp.12422
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tamoxifen-induced hepatotoxicity by tamoxifen–phospholipid complex

Abstract: Data of the present study suggests that phospholipid may prove as a useful component of combination therapy in cancer patients under the TMX treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In vivo administration of the SYK inhibitor prevented SYK activation (pSYK Y525/526 levels) induced by chronic alcohol feeding (Fig. A) …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In vivo administration of the SYK inhibitor prevented SYK activation (pSYK Y525/526 levels) induced by chronic alcohol feeding (Fig. A) …”
Section: Resultsmentioning
confidence: 94%
“…Because of embryonic lethality, studies with SYK knockouts are limited . The available SYK conditional knockout mice with inducible SYK inactivation by tamoxifen also has limitations for ALD given the known adverse effects of tamoxifen on the liver …”
Section: Discussionmentioning
confidence: 99%
“…Animals of all groups were sacrificed by cervical decapitation under light ether anaesthesia on the 22nd day. Blood and liver samples were collected and processed accordingly for the estimation of antioxidant enzymes . Postmitochondrial supernatant was prepared as per the previously reported method and used for the assay of marker enzymes, namely reduced glutathione (GSH), glutathione peroxidase (GPx), superoxide dismutase (SOD) and catalase (CAT) as per the reported methods .…”
Section: Methodsmentioning
confidence: 99%
“…Long‐term TMX therapy has some major side effects, including higher prevalence of endometrial cancer, thromboembolic disorders, liver cancer and development of drug resistance . Very recently, we demonstrated that TMX metabolism in the liver leads to oxidative liver damage …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation